Disulfiram Transcends ALDH Inhibitory Activity When Targeting Ovarian Cancer Tumor-Initiating Cells - Caminear, Michael W.; Harrington, Brittney S.; Kamdar, Rahul D.; Kruhlak, Michael J.; Annunziata, Christina M. (Frontiers in Oncology, 2022)
Epithelial ovarian cancer (EOC) is a global health burden and remains the fifth leading cause of cancer related death in women worldwide with the poorest five-year survival rate of the gynecological malignancies. EOC recurrence is considered to be driven by the survival of chemoresistant, stem-like tumor-initiating cells (TICs). We previously showed that disulfiram, an ALDH inhibitor, effectively targeted TICs compared to adherent EOC cells in terms of viability, spheroid formation, oxidative stress and also prevented relapse in an in vivo model of EOC. In this study we sought to determine whether specific targeting of ALDH isoenzyme ALDH1A1 would provide similar benefit to broader pathway inhibition by disulfiram. NCT-505 and NCT-506 are isoenzyme-specific ALDH1A1 inhibitors whose activity was compared to the effects of disulfiram. Following treatment with both the NCTs and disulfiram, the viability of TICs versus adherent cells, sphere formation, and cell death in our in vitro relapse model were measured and compared in EOC cell lines. We found that disulfiram decreased the viability of TICs significantly more effectively versus adherent cells, while no consistent trend was observed when the cells were treated with the NCTs. Disulfiram also affected the expression of proteins associated with NFκB signaling. Comparison of disulfiram to the direct targeting of ALDH1A1 with the NCTs suggests that disulfiram’s broader cellular effects are more suitable as a therapeutic to eradicate TICs from tumors and prevent EOC relapse. In addition to providing insight into a fitting treatment for TICs, the comparison of disulfiram to NCT-505 and -506 has increased our understanding of disulfiram’s mechanism of action. Further elucidation of disulfiram’s mechanism has the potential to reveal additional targets to treat EOC TICs and prevent disease recurrence.